Lead Compounds from Mangrove-Associated Microorganisms - Ancheeva, Elena (Mar Drugs, 2018)
The mangrove ecosystem is considered as an attractive biodiversity hotspot that is intensively studied in the hope of discovering new useful chemical scaffolds, including those with potential medicinal application. In the past two decades, mangrove-derived microorganisms, along with mangrove plants, proved to be rich sources of bioactive secondary metabolites as exemplified by the constant rise in the number of publications, which suggests the great potential of this important ecological niche. The present review summarizes selected examples of bioactive compounds either from mangrove endophytes or from soil-derived mangrove fungi and bacteria, covering the literature from 2014 to March 2018. Accordingly, 163 natural products are described in this review, possessing a wide range of potent bioactivities, such as cytotoxic, antibacterial, antifungal, α-glucosidase inhibitory, protein tyrosine phosphatase B inhibitory, and antiviral activities, among others.